ATER em assentamentos de reforma agrária em Santa Catarina: o conteúdo das orientações técnicas - Louzada, José Antonio (2015)
This research aims to analyze the content of ATER activities for agrarian reform settlements in Santa Catarina from the February-2014-to-February-2015 contract period. In this context, this study seeks to reflect the extension activities based on different conceptions of extension. The research is quantitative and is characterized as a descriptive study of NOs of Abelardo Luz and Calmon. Therefore, it has used the Frequential method, of an approximation of the content analysis method, literature review, documents discussing national and Santa Catarina ATER and consultation on the database of SIATER and SIGRA. In this context, the contents analyzed were those of individual and collective methods of rural extension that focused on the productive, social and environmental axes. Therefore, visits and office visits formed the category of individual activities while the analyzed collectives were the meetings of interest to the community, courses, field days, demonstration units and exchanges. From the survey data it was found that the technical guidelines, both with use of individual and collective methods were guided by the dynamics of the consolidated production system in the different regions. In addition, research also confronted SIATER data (2014) and SIGRA (2014) and found that they converge partially. In this sense, it can be inferred that the technical guidelines are being built with farmers in part. However, when it refers to technical teams, they held guidelines that move to a participatory conception of rural extension technical support. Another observation is that the SIGRA has contributed to the technical teams for planning, execution, monitoring and evaluation of activities of ATER. Therefore a differentiated ATER of diffusionist conception goes through reciprocal knowledge and dialogue between experts and farmers, so that they may be agents of transformation in the reality in which they operate.